Genotype-specific variation in West Nile virus dispersal in California - Duggal, Nisha K. (Virology, 2015)
West Nile virus (WNV) is an arbovirus that was first reported in North America in New York in 1999 and, by 2003, had spread more than 4,000 km to California. However, variation in viral genetics associated with spread are not well understood. Herein, we report sequences for more than 100 WNV isolates made from mosquito pools that were collected from 2003 – 2011 as part of routine surveillance by the California Mosquito-borne Virus Surveillance System. We performed phylogeographic analyses and demonstrated that 5 independent introductions of WNV (1 WN02 genotype strain and 4 SW03 genotype strains) occurred in California. The SW03 genotype of WNV was constrained to the southwestern U.S. and had a more rapid rate of spread. In addition, geographic constraint of WNV strains within a single region for up to 6 years suggest viral maintenance has been driven by resident, rather than migratory, birds and overwintering in mosquitoes.